The Late Pleistocene Bokhan site (Fore-Baikal area, Russia) and its palaeoenvironmental reconstruction. (December 2019) - Khenzykhenova, Fedora; Yoshida, Kunio; Sato, Takao; Shchetnikov, Alexander; Osipova, Evgenia; Danukalova, Guzel; Ivanova, Varvara; Simakova, Alexandra; Filinov, Ivan; Semenei, Elena; Namzalova, Oyuna; Tumurov, Erdem; et al.
Abstract: Multidisciplinary research was carried out at the new Late Pleistocene Bokhan site in the Baikal region (Fore-Baikal) including geochemical and petrochemical X-ray fractions, palynological and palaeozoological studies, and AMS-dating. Four palynological complexes show a development of vegetation from open meadow-steppe landscapes that are replaced by meadow steppe with small areas of tundra vegetation to pine and pine-birch boreal forests. The fauna included molluscs, reptile and mammals of tundra, steppe and taiga inhabitants. It is a so-called no-analogue fauna extant analogy of species composition which reflects tundra-steppe landscapes in conditions of cold and dry climate during Sartanian time (MIS 2) (layers 1–2) and tundra-forest-steppe landscapes with more comfortable climatic conditions, during the end of The Pleistocene (layer 3).